Propuesta para la remediación de suelos afectados por el sector minero en Yalí Antioquia, Colombia mediante la cáscara de Manihot Esculenta (2023)
This project is developed due to the need to reduce the levels of metals absorbed by the soil after the mining extraction process. Mining is one of the main activities that promote the economy of countries, because mining reduces unemployment and in turn allows income to be equitable for the population, additionally, it allows us the innovation of resources that allow development, This is because mining activity is present throughout the food chain, which is why by increasing mining development, other sectors benefit and allow for an increase in the income of said country. However, for this occurs, it is essential that the activity be regulated, so that when carrying out any type of extraction, the impacts that this process may generate on the environment or the health of living beings are minor.